Mathematical modeling and digital design of an intensified filtration-washing-drying unit for pharmaceutical continuous manufacturing. (23rd November 2021) - Destro, Francesco; Hur, Inyoung; Wang, Vivian; Abdi, Mesfin; Feng, Xin; Wood, Erin; Coleman, Simon; Firth, Paul; Barton, Alastair; Barolo, Massimiliano; Nagy, Zoltan K.
Highlights: Mathematical model of carousel for continuous slurry filtration, washing and drying. Multi-component differential mass, energy and momentum balances. Experimental model calibration to isolation of paracetamol crystals. Identification of probabilistic design space with calibrated model. Assessment of maximum throughput conditions in the design space. Abstract: This paper introduces a comprehensive mathematical model of a novel integrated filter-dryer carousel system, designed for continuously filtering, washing and drying a slurry stream into a crystals cake. The simulator includes models for dead-end filtration, cake washing and convective cake drying, based on dynamic multi-component mass, energy and momentum balances. For a set of feed conditions and control inputs, the model allows tracking the solvents and impurities content in the cake (critical quality attributes, CQAs) throughout the whole process. The filtration and drying model parameters were identified for the isolation of paracetamol from a crystallization slurry. The calibrated model was used for designing the isolation of paracetamol from a multi-component slurry, containing a non-volatile impurity, too. The probabilistic design space, expressing the combinations of the carousel feed conditions and control inputs for which the probability of meeting the target CQAs is acceptable, and the maximum throughput were identified.